2016
DOI: 10.1111/ijfs.13245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differently processed açai (Euterpe oleracea Mart.) on the retention of phenolics and anthocyanins in chewy candies

Abstract: Summary This study investigated the effects of processing and storage on the physicochemical properties and retention of antioxidant compounds of no‐added sucrose chewy candies (NASC) incorporated with differently processed açai (frozen pulp, spray‐dried and freeze‐dried powders). NASC containing freeze‐dried açai had the highest softness and recoveries of total phenolic (TP) and total anthocyanin (TA) immediately after production. Colour parameters and antioxidant capacity by ABTS and ORAC assays had no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…However, the GAE level was only dose-dependent in the RE146 candies perhaps owing to the contribution to GAE of other ingredients. da Silva et al (2016) [38] found GAE recovery percentages ranging from 72% to 78% in chewy candies made with acai and no added sucrose. The GAE levels found in our study for the medium-RE74 and RE146 candies (227 and 572 mg GAE/100 g, respectively) were coherent with those reported in jelly candies containing tea extracts at 10-15 g/kg (246-1256 mg GAE/100 g) [11], and in sugar candies based on polyalcohols and ascorbic acid (2 g/kg) with menthe or camomile extracts (222-408 mg GAE/100 g) [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the GAE level was only dose-dependent in the RE146 candies perhaps owing to the contribution to GAE of other ingredients. da Silva et al (2016) [38] found GAE recovery percentages ranging from 72% to 78% in chewy candies made with acai and no added sucrose. The GAE levels found in our study for the medium-RE74 and RE146 candies (227 and 572 mg GAE/100 g, respectively) were coherent with those reported in jelly candies containing tea extracts at 10-15 g/kg (246-1256 mg GAE/100 g) [11], and in sugar candies based on polyalcohols and ascorbic acid (2 g/kg) with menthe or camomile extracts (222-408 mg GAE/100 g) [13].…”
Section: Discussionmentioning
confidence: 99%
“…Aware of this problem, the confectionary industry is making efforts to develop new products with better nutritional properties that will meet the demands of consumers regarding a healthier diet [ 3 ]. The most common strategies used in improving candy formulations involve replacing sugars with sweeteners [ 4 , 5 ]; the substitution of azo dyes for natural ones [ 6 , 7 ]; or the incorporation of dietary fibre, vitamins, fruit derivatives, and plant extracts [ 7 , 8 , 9 , 10 ]. Regarding the latter, different studies on candies made with phenolic extracts of tea [ 11 ], bougainvillea [ 12 ], mint and chamomile [ 13 ] revealed their potential for inclusion as antioxidants or nutraceutical ingredients in candies.…”
Section: Introductionmentioning
confidence: 99%
“…Essas diferenças podem ser explicadas devido ao tipo de polpa utilizada em cada trabalho, onde cada polpa apresenta características físico-químicas típicas de cada fruto, e também pelas diferenças dos parâmetros de processamento. Silva et al (2016) quantificaram o conteúdo de compostos fenólicos e de antocianinas, e a atividade antioxidante pela captura do radical DPPH˚, em estudos com balas mastigáveis diet produzidas com polpa de açaí congelada. Os autores apresentaram valores superiores ao presente estudo, onde encontraram 252,65 ± 15,72 mg de ácido gálico 100 g -1 , 13,28 ± 0,23 mg 100 g -1 e 3,83 ± 0,02 μmol 100 g -1 , respectivamente.…”
Section: Discussionunclassified
“…Antioxidants are compounds that may prevent or delay some types of cell damage in the human body exposed to free radical action (Bagchi et al, 2000;Moo-Huchin et al, 2015;Oroian & Escriche, 2015). So, the consumption of antioxidants derived from natural sources, especially fruits and vegetables, can improve nutrition and can also have preventive effects against cancer, cardiovascular diseases and neuropathies (Rufino et al, 2011;Souza et al, 2012;Moo-Huchin et al, 2015;Silva et al, 2016). Nowadays, new potential natural sources of antioxidants have been exploited as an alternative to complement the diet with natural, healthy and lower cost compounds.…”
Section: Introductionmentioning
confidence: 99%